Health‐related empowerment in cancer: Validity of scales from the Health Education Impact Questionnaire. Issue 20 (2nd July 2014) - Maunsell, Elizabeth; Lauzier, Sophie; Brunet, Jennifer; Pelletier, Sylvie; Osborne, Richard H.; Campbell, H. Sharon
Abstract : BACKGROUND: Empowerment refers to an individual's feelings of being able to manage the challenges of the cancer experience and of having a sense of control over one's life. However, empowerment questionnaires that have been validated for the cancer setting are lacking. The objective of this study was to validate scales from the Health Education Impact Questionnaire (heiQ), which assesses the effects of health education programs among individuals with chronic conditions. The heiQ scales Social integration and support, Health service navigation, Constructive attitudes and approaches, Skill and technique acquisition, and Emotional distress were identified as key dimensions of empowerment for the cancer context. METHODS: Adults who were diagnosed with cancer <3 years earlier were recruited from a population‐based cancer registry and from the Canadian Cancer Society's information and peer‐support programs. The 731 participants completed a mailed questionnaire, which included the heiQ scales, related constructs, and demographics. Reliability was assessed using Cronbach α values, and validity was determined using confirmatory factor analysis and scale correlations with related constructs (self‐efficacy, intrusive thoughts about cancer, and mental and physical health). RESULTS: The hypothesized 5‐factor model fit the data adequately (chi‐square statistic, 528.17; degrees of freedom, 265; root mean square error of approximation, .04; non‐normed fit index, .99; comparative fit index, 1.00; standardized root mean residual, .05). Factor loadings were high (23 of 25 were ≥.70), and the factor correlations indicated separate but related constructs. Cronbach α values ranged from .75 to .90. A priori hypotheses about the correlations between heiQ scales and related constructs all were supported. CONCLUSIONS: The current results support the validity of these 5 heiQ scales as generic measures of health‐related empowerment in the cancer setting. These scales could fill an important gap in the measures currently available to evaluate proximal effects of support interventions. Cancer 2014;120:3228–3236. © 2014 American Cancer Society . Abstract : The current results support the validity of 5 Health Education Impact Questionnaire (heiQ) scales ( Social integration and support, Health service navigation, Constructive attitudes and approaches, Skill and technique acquisition, and Emotional distress ) as generic measures of health‐related empowerment in the cancer setting. These scales could fill an important gap in the measures currently available to evaluate the proximal effects of support interventions.